Sistem Pendukung Keputusan Dalam Penilaian Kinerja Supervisor Menggunakan Metode COPRAS Dengan Pembobotan ROC - Agung Triayudi; Fifto Nugroho; Andreas Gerhard Simorangkir; Mesran Mesran (Journal of Computer System and Informatics (JoSYC), 2022)
Supervisors are direct supervisors of leaders and operators who have duties and responsibilities, namely providing direction or work planning in accordance with existing SOPs in the company and monitoring the work of leaders and operators properly. In this study, so far the company in evaluating the performance of the supervisor is done manually, that is, the company only judges based on the length of time the supervisor has worked. In fact, the supervisor's performance appraisal is an ineffective performance appraisal. Therefore, the company must make several other performance assessments such as Length of Work, Leadership, Communication, Discipline and Attendance. In evaluating the supervisor's performance, a decision support system (DSS) is needed. The method used in this study is the COPRAS method with ROC weighting. The calculation of the COPRAS method with ROC weighting can produce the best alternative, namely alternative A2 on behalf of "Budiman Sianipar, ST" with a value of Ui = 100